GAMBARAN LUARAN HASIL PERSALINAN PADA PASIEN PREEKLAMSIA-EKLAMSIA DI RSUD DR SOEDARSO PERIODE 1 JANUARI 2011-31 DESEMBER 2011 - ., Riris Putri Marito Sinaga (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. Preeclamsia is a pregnancy-specific syndrome whichreduce organ perfusion because of vasospasm and endothelial activation.The combination of proteinuria and hypertension during pregnancy willincrease the risk of perinatal and maternal mortality and morbidity. Objective. This research would characterized patient, neonatal outcomeand maternal outcome at dr. Soedarso General Hospital Pontianak. Method. This research is a descriptive study. The sample was taken bynon probability sampling with consecutive sampling. This research was carried out at dr. Soedarso General Hopital on December 2011-June2012. The data were taken from Medical Record at dr. Soedarso GeneralHospital Pontianak. Result. Total case of preeclamsia-eclamsia were 275 patient which 219maternal and 232 neonatal became the sample of this research. Characteristic of patients was mostly on 20-30 years old patiens (18,7%),nullipara (39,7%) and gestational age >37 weeks (78,1%). Neonataloutcome with severe asphyxia was 9,1% and moderate ashpyxia was16,3%. Morbidity on maternal was 23,7%, which are hypertensiveretinopathy (5,9%), solutio placenta (1,8%), pain in epigastric regio (1,4%),pulmonary edema (0,9%), HELLP syndrome (0,5%), postpartum eclamsia(0,5%), hemiparesis sinistra and NVII peripheral lesion (0,5%), dyspnea(0,5%), decompensation cordis (0,5%), hematoma placenta (0,5%) andascites (0,5%). Maternal mortality was 0,9% and neonatal mortality was9,9%. Conclusion. The characterize of maternal preeclamptic-eclamptic patientswas 20-30 years old, nullipara and gestational age >37 weeks.Preeclamsia-eclamsia cause morbidity and mortality on neonatal andmaternal. Keyword: Preeclamsia-eclamsia, neonatal outcome, maternal outcome1. Medical School, Faculty of Medicine, University of Tanjungpura Pontianak, West Kalimantan2. Department of Obstetrics and Gynecology, dr. Soedarso General Hospital Pontianak, West Kalimantan3. Departement of Parasitology, Medical School, Faculty of Medicine, University of Tanjungpura, Pontianak, West Kalimantan